X(15x+11x)+2=0

Simple and best practice solution for X(15x+11x)+2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(15x+11x)+2=0 equation:


Simplifying
X(15x + 11x) + 2 = 0

Combine like terms: 15x + 11x = 26x
X(26x) + 2 = 0

Remove parenthesis around (26x)
X * 26x + 2 = 0

Reorder the terms for easier multiplication:
26X * x + 2 = 0

Multiply X * x
26xX + 2 = 0

Reorder the terms:
2 + 26xX = 0

Solving
2 + 26xX = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 26xX = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 26xX = 0 + -2
26xX = 0 + -2

Combine like terms: 0 + -2 = -2
26xX = -2

Divide each side by '26X'.
x = -0.07692307692X-1

Simplifying
x = -0.07692307692X-1

See similar equations:

| 4.9t^2-24.5t+2=0 | | c^2-3c-18= | | 6+3(13-2)-25= | | 5x+2-4x=5+8 | | -5y+7y=10 | | 2(4p+3)-3(3p-6)-16p= | | -6(7x-1)=-8x+9(-3x+4) | | .5(4m+5)=-6 | | t^2-24.5t+2=0 | | 2a/3a-3/4=3a/4a | | h(t)=-16t^2+20t+4 | | 7+3a=11-a | | 3(4x-6)=2(4x-3)-(x+8) | | 13.04=f+8.25 | | 9n-3n= | | 13(t+1)-3(2+4t)=48 | | 180=(9x+4)-y | | -15=-5t^2+30t | | 9-3x+5x=-11 | | 2-(x+3)=6 | | 5x+4=37 | | X^2+6x-34=0 | | y+x=y-x | | 2(x-5)+2x=x+3x-2x | | 180+(9x+4)=y | | 20-0.75x+0.55x=10 | | 55+8(25)=x | | 55+8=25 | | -1x^2+4=2x^2-5 | | -20=-10(x+12) | | .40=.5-12 | | 9x-8=9x+6 |

Equations solver categories